RNAi screening identifies Trypanosoma brucei stress response protein kinases required for survival in the mouse - Fernandez-Cortes, Fernando; Serafim, Tiago D.; Wilkes, Jonathan M.; Jones, Nathaniel G.; Ritchie, Ryan; McCulloch, Richard; Mottram, Jeremy C. (Scientific reports, 2017)
Protein kinases (PKs) are a class of druggable targets in Trypanosoma brucei , the causative agent of Human African Trypanosomiasis (sleeping sickness), yet little is known about which PKs are essential for survival in mammals. A recent kinome-wide RNAi screen with 176 individual bloodstream form Trypanosoma brucei lines identified PKs required for proliferation in culture. In order to assess which PKs are also potential virulence factors essential in vivo , lines were pooled, inoculated into mice, and screened for loss of fitness after 48 h RNAi. The presence of trypanosomes in the bloodstream was assessed using RNAi target sequencing (RITseq) and compared to growth in culture. We identified 49 PKs with a significant loss of fitness in vivo in two independent experiments, and a strong correlation between in vitro and in vivo loss of fitness for the majority. Nine PKs had a more pronounced growth defect in vivo , than in vitro . Amongst these PKs were several with putative functions related to stress responses mediated through the PI3K/TOR or MAPK signaling cascades, which act to protect the parasite from complement-mediated and osmotic lysis. Identification of these virulence-associated PKs provides new insights into T. brucei -host interaction and reveals novel potential protein kinase drug targets.